Advances in the regulation of adipogenesis and lipid metabolism by exosomal ncRNAs and their role in related metabolic diseases - Liu, Cong; Liu, Xilin; Li, Hong; Kang, Zhichen (Frontiers in Cell and Developmental Biology, 2023)
Exosomes are membrane-bound extracellular vesicles released following the fusion of multivesicular bodies (MVBs) with the cell membrane. Exosomes transport diverse molecules, including proteins, lipids, DNA and RNA, and regulate distant intercellular communication. Noncoding RNA (ncRNAs) carried by exosomes regulate cell-cell communication in tissues, including adipose tissue. This review summarizes the action mechanisms of ncRNAs carried by exosomes on adipocyte differentiation and modulation of adipogenesis by exosomal ncRNAs. This study aims to provide valuable insights for developing novel therapeutics.